Biotransformation of a potent anabolic steroid, mibolerone, with Cunninghamella blakesleeana, C. echinulata, and Macrophomina phaseolina, and biological activity evaluation of its metabolites - Siddiqui, Mahwish (PLoS One, 2017)
Seven metabolites were obtained from the microbial transformation of anabolic-androgenic steroid mibolerone (1) with Cunninghamella blakesleeana, C. echinulata, and Macrophomina phaseolina. Their structures were determined as 10β,17β-dihydroxy-7α,17α-dimethylestr-4-en-3-one (2), 6β,17β-dihydroxy-7α,17α-dimethylestr-4-en-3-one (3), 6β,10β,17β-trihydroxy-7α,17α-dimethylestr-4-en-3-one (4), 11β,17β-dihydroxy-(20-hydroxymethyl)-7α,17α-dimethylestr-4-en-3-one (5), 1α,17β-dihydroxy-7α,17α-dimethylestr-4-en-3-one (6), 1α,11β,17β-trihydroxy-7α,17α-dimethylestr-4-en-3-one (7), and 11β,17β-dihydroxy-7α,17α-dimethylestr-4-en-3-one (8), on the basis of spectroscopic studies. All metabolites, except 8, were identified as new compounds. This study indicates that C. blakesleeana, and C. echinulata are able to catalyze hydroxylation at allylic positions, while M. phaseolina can catalyze hydroxylation of CH(2) and CH(3) groups of substrate 1. Mibolerone (1) was found to be a moderate inhibitor of β-glucuronidase enzyme (IC(50) = 42.98 ± 1.24 μM) during random biological screening, while its metabolites 2–4, and 8 were found to be inactive. Mibolerone (1) was also found to be significantly active against Leishmania major promastigotes (IC(50) = 29.64 ± 0.88 μM). Its transformed products 3 (IC(50) = 79.09 ± 0.06 μM), and 8 (IC(50) = 70.09 ± 0.05 μM) showed a weak leishmanicidal activity, while 2 and 4 were found to be inactive. In addition, substrate 1 (IC(50) = 35.7 ± 4.46 μM), and its metabolite 8 (IC(50) = 34.16 ± 5.3 μM) exhibited potent cytotoxicity against HeLa cancer cell line (human cervical carcinoma). Metabolite 2 (IC(50) = 46.5 ± 5.4 μM) also showed a significant cytotoxicity, while 3 (IC(50) = 107.8 ± 4.0 μM) and 4 (IC(50) = 152.5 ± 2.15 μM) showed weak cytotoxicity against HeLa cancer cell line. Compound 1 (IC(50) = 46.3 ± 11.7 μM), and its transformed products 2 (IC(50) = 43.3 ± 7.7 μM), 3 (IC(50) = 65.6 ± 2.5 μM), and 4 (IC(50) = 89.4 ± 2.7 μM) were also found to be moderately toxic to 3T3 cell line (mouse fibroblast). Interestingly, metabolite 8 showed no cytotoxicity against 3T3 cell line. Compounds 1–4, and 8 were also evaluated for inhibition of tyrosinase, carbonic anhydrase, and α-glucosidase enzymes, and all were found to be inactive.